'I am dead': Cotard syndrome and dementia. (3rd April 2019) - Cipriani, Gabriele; Nuti, Angelo; Danti, Sabrina; Picchi, Lucia; Di Fiorino, Mario
Abstract: Background: Cotard syndrome is a rare condition whose main feature is a nihilistic delusion ranging from the denial of body parts to that of the existence of one's own life or even the entire universe. Objectives: The aim of this article is to review the nosological significance of Cotard syndrome and to explore the disorder among patients with dementia. Methods: Medline and Google Scholar searches were conducted for relevant articles, chapters and books published before 2018. Search terms used included Cotard delusion, Cotard syndrome and dementia, nihilistic delusion. Publications found through this indexed search were reviewed for further relevant references. Results and conclusion: In this narrative review we emphasise the fact that cases of Cotard syndrome involving patients with dementia are reported quite infrequently. Published studies are limited to very short series or isolated cases. Clinicians are obliged to treat the disorder. They should be alert to the potential high risk inherent in this condition. Keypoints: Cotard syndrome is a rare condition characterised by nihilistic delusions that may range from negation of existence of parts of the body to delusion of being dead. The prevalence and incidence of this rare syndrome are not known. Since Cotard's syndrome is conceptualised as part of an underlying disorder, several psychiatric and somatic diseases have been associated with the syndrome. The syndrome may occur in patients suffering from dementia.